PENGARUH KEAHLIAN AUDITOR, TEKANAN KETAATAN DAN INDEPENDENSI PADA AUDIT JUDGMENT - Drupadi, Made Julia; Sudana, I Putu (E-Jurnal Akuntansi, 2016)
Audit judgment is an objective assessment of an auditor of the information from the audit evidence obtained and influenced by aspects indivindu auditors so as to produce thought or decision on information obtained previously. Auditor expertise, pressure obedience, and independence are aspects indivindu assessed could affect audit judgment. The purpose of this study,was to determine the effect auditor expertise, pressure obedience and independence of the audit judgment. The samples used as many as 57 respondents to the sampling method of determining the sample is saturated. Methods of data collection is done by questionnaire. The data analysis technique used is the technique of multiple linear regression analysis. The results obtained are the expertise and independence of the auditor positive effect on audit judgment. Pressure obedience negative effect on audit judgment.
Keywords: audit judgment, expertise auditor, pressure obedience, independence